2011
DOI: 10.1017/s0025315411000932
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and genetic variation in the North Atlantic copepod,Centropages typicus

Abstract: This study describes phenotypic and genotypic variations in the planktonic copepod, Centropages typicus (Copepoda: Calanoida) that indicate differentiation between geographical samples. We found consistent differences in the morphology of the chela of the sexually modified fifth pereiopod (P5) of male C. typicus between samples from the Mediterranean, western North Atlantic and eastern North Atlantic. A 560 base pairs (bp) region of the C. typicus mitochondrial cytochrome c oxidase subunit I (COI) and a 462 bp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
1
12
1
Order By: Relevance
“…These results agree with the conclusions inferred from morphological characteristics by Castellani et al . (), but contradict the molecular results from the same study, which indicated lack of genetic structure across the entire distributional range of the species (Castellani et al . ).…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…These results agree with the conclusions inferred from morphological characteristics by Castellani et al . (), but contradict the molecular results from the same study, which indicated lack of genetic structure across the entire distributional range of the species (Castellani et al . ).…”
Section: Discussioncontrasting
confidence: 55%
“…(), but contradict the molecular results from the same study, which indicated lack of genetic structure across the entire distributional range of the species (Castellani et al . ). In contrast, our finding of significant genetic structure reflects the power and potential of next‐generation technologies to resolve highly sensitive and specific molecular genetic markers, such as RAD tags (Reitzel et al .…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…data). Similarly, a study of the copepod, Centropages typicus, by Blanco-Bercial and Bucklin (2016) using 1,000s of genomic SNPs obtained by RAD-seq revealed evidence of population structure, in contrast to an earlier study based on mitochondrial gene sequences (Castellani et al 2012). …”
Section: From Population Genetics To Population Genomicsmentioning
confidence: 84%